Reduction of the cytosolic fructose-1,6-bisphosphatase in transgenic potato plants limits photosynthetic sucrose biosynthesis with no impact on plant growth and tuber yield - Sonnewald, Uwe; et al. (Plant Journal, 1996)
A 45% reduction of the cytosolic FBPase activity did not cause any measurable change in metabolite concentrations, growth behaviour or photosynthetic parameters of the transgenic plants. Inhibition of cytosolic FBPase activity below 20% of the wild-type activity led to an accumulation of 3-PGA, triose-phosphates and fructose-1,6-bisphosphate in source leaves. This resulted in a reduced light-saturated rate of assimilation measured via gas exchange and a decreased photosynthetic rate under conditions of the leaf disc electrode with saturating light and CO2. Measuring photosynthetic carbon fluxes by labelling leaf discs with (CO2)-C-14 revealed a 53-65% reduction of sucrose synthesis whereas starch synthesis decreased only by 18-24%. The flux into the anionic and cationic fraction was not altered. Despite these changes steady-state sucrose concentrations were not effected in source leaves from transgenic plants. Starch accumulated by more than a factor of 3 compared with wild-type leaves and was degraded during the night. This provides strong evidence for the hypothesis that hexoses and/or hexosephosphates are exported out of the chloroplasts, thereby circumventing the limitation of sucrose biosynthesis caused by the inhibition of cytosolic FBPase in the dark. Accordingly, plant growth and potato tuber yield remained unaltered. From these data it can be concluded that a reduced photosynthetic sucrose biosynthetic capacity can be efficiently compensated without any reduction in crop yield under greenhouse or growth chamber conditions by changing carbon export strategy. Whether the same holds true for field conditions remains to be elucidated.